For the throne - Whitten, Hannah (Whitten, Hannah. Wilderwood, 2022)
"Red and the Wolf have finally contained the threat of the Old Kings but at a steep cost. Red's beloved sister Neve, the First Daughter is lost in the Shadowlands, an inverted kingdom where the vicious gods of legend have been trapped for centuries and the Old Kings have slowly been gaining control. But Neve has an ally--though it's one she'd rather never have to speak to again--the rogue king Solmir. Solmir wants to bring an end to the Shadowlands and he believes helping Neve may be the key to its destruction. But to do that, they will both have to journey across a dangerous landscape in order to find a mysterious Heart Tree, and finally to claim the gods' dark, twisted powers for themselves"--